Саламат бала тәрбиясында ертеклердиң әҳмийети - Бекимбетова, Г (SCIENCE and SOCIETY, 2017)
The article deals with the study of teaching good and evil with the help of fairy tales in Karakalpak folk Pedagogy of the children of pre-school age, the rules of their use and relationship between people. The work contains different points of view on the issues of education that are important for preschool teachers and parents.
Keywords: folk pedagogy; freedom of speech; fairy tales; thought; knowledge; skills; intellectual development; attention; good; evil; mercy